Rutinitas H{alaqah QiraN Di Pondok Pesantren Zainul Ibad Prenduan Sumenep Madura) - Ghozi Mubarok; Lidia Candra Sari (Dirosat : Journal of Islamic Studies, 2019)
The focus of the problems that will be discussed in this research article are first, what is the background of the routine activities of the h}alaqah qira>'ah sab'ah at Zainul Ibad Prenduan Islamic Boarding School? second, how is the implementation of the routine activities of the h}alaqah qira>'ah sab'ah at the Zainul Ibad Prenduan Islamic Boarding School? To answer the questions above, this study was designed using a qualitative approach with a phenomenological research type. The data collection techniques used in this study were observation, interviews, and documentation, while the researchers were the key instruments and took caretakers of the Zainul Ibad Prenduan Islamic boarding school and several female students to serve as research samples. From the results of this study it was found that first, the background to the routine activities of the h}alaqah qira>'ah sab'ah is to add insight and basic knowledge for female students and to maintain the preservation of the qira>'ah sab'ah science so that it does not become extinct and is always in the memory of Kyai and his students. Second, the method used in the process of routine halaqah qira>'ah sab'ah activities uses the jama' kubra> or t}ori>qotul jama>'i stages method, which is a system of combining the seven qurra>' imams. This process is carried out by talaqqi per verse according to the order of the Imam in one meeting every week as much as one page. When analyzed, if the learning process takes place in 20 meetings, then the learning will complete 1 juz